In SARS-CoV-2 delta variants, Spike-P681R and D950N promote membrane fusion, Spike-P681R enhances spike cleavage, but neither substitution affects pathogenicity in hamsters - Furusawa, Yuri; Kiso, Maki; Iida, Shun; Uraki, Ryuta; Hirata, Yuichiro; Imai, Masaki; Suzuki, Tadaki; Yamayoshi, Seiya; Kawaoka, Yoshihiro (EBioMedicine, 2023)
The SARS-CoV-2 delta (B.1.617.2 lineage) variant was first identified at the end of 2020 and possessed two unique amino acid substitutions in its spike protein: S-P681R, at the S1/S2 cleavage site, and S-D950N, in the HR1 of the S2 subunit. However, the roles of these substitutions in virus phenotypes have not been fully characterized. We used reverse genetics to generate Wuhan-D614G viruses with these substitutions and delta viruses lacking these substitutions and explored how these changes affected their viral characteristics in vitro and in vivo. S-P681R enhanced spike cleavage and membrane fusion, whereas S-D950N slightly promoted membrane fusion. Although S-681R reduced the virus replicative ability especially in VeroE6 cells, neither substitution affected virus replication in Calu-3 cells and hamsters. The pathogenicity of all recombinant viruses tested in hamsters was slightly but not significantly affected. Our observations suggest that the S-P681R and S-D950N substitutions alone do not increase virus pathogenicity, despite of their enhancement of spike cleavage or fusogenicity. A full list of funding bodies that contributed to this study can be found under Acknowledgments.